Study on Clinico-Haematol-Biochemical Alterations in Goats Suffering from Trichostrongylosis in Anand District of Gujara - Rajpura, NR; Mandali, GC; Rao, Neha; Patel, AC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This cross-sectional study was aimed at determining the effect of trichostrongylosis on clinical, hematological, and biochemical parameters in goats. The study included eight healthy control goats and 48 naturally infected goats from the Anand district of Gujarat. The cases having a history of diarrhea, anorexia, weakness, dullness, loss of weight, and not dewormed were selected. Fecal samples of infected goats were examined by direct smear method for the presence of Trichostrongylus spp. eggs and the infection was confirmed by quantitative evaluation and coproculture of the samples for the identification of larvae. The result indicated that the infected goats had significantly elevated rectal temperature, pulse rate, and respiration rate along with diarrhea, dullness, depression, emaciation, and loss of condition. Moreover, there was a significant decrease in the mean Hb, TEC, PCV, lymphocyes, as well as serum total protein, calcium and phosphorus, and a significant increase in TLC, neutrophils, eosinophils, ALT, AST and ALP in infected goats.